Cell-Free Glycoengineering of the Recombinant SARS-CoV-2 Spike Glycoprotein - Ruhnau, Johannes; Grote, Valerian; Juarez-Osorio, Mariana; Bruder, Dunja; Mahour, Reza; Rapp, Erdmann; Rexer, Thomas F. T.; Reichl, Udo (Frontiers in Bioengineering and Biotechnology, 2021)
The baculovirus-insect cell expression system is readily utilized to produce viral glycoproteins for research as well as for subunit vaccines and vaccine candidates, for instance against SARS-CoV-2 infections. However, the glycoforms of recombinant proteins derived from this expression system are inherently different from mammalian cell-derived glycoforms with mainly complex-type N-glycans attached, and the impact of these differences in protein glycosylation on the immunogenicity is severely under investigated. This applies also to the SARS-CoV-2 spike glycoprotein, which is the antigen target of all licensed vaccines and vaccine candidates including virus like particles and subunit vaccines that are variants of the spike protein. Here, we expressed the transmembrane-deleted human β-1,2 N-acetlyglucosamintransferases I and II (MGAT1ΔTM and MGAT2ΔTM) and the β-1,4-galactosyltransferase (GalTΔTM) in E. coli to in-vitro remodel the N-glycans of a recombinant SARS-CoV-2 spike glycoprotein derived from insect cells. In a cell-free sequential one-pot reaction, fucosylated and afucosylated paucimannose-type N-glycans were converted to complex-type galactosylated N-glycans. In the future, this in-vitro glycoengineering approach can be used to efficiently generate a wide range of N-glycans on antigens considered as vaccine candidates for animal trials and preclinical testing to better characterize the impact of N-glycosylation on immunity and to improve the efficacy of protein subunit vaccines.